Learn to program with Phrogram! : a guide to learning through game programming using the latest version of kids programming language - Schwartz, Jon (Addison Wesley Professional, 2007)
"This guide will quickly and easily walk complete beginners through creating their first simple games using Phrogram. The material is friendly and approachable to the young and to the technologically timid alike."--Alfred Thompson, Academic Relations Manager, Microsoft Corporation Different programming languages give you different ways to tell your computer what to do. If you are just starting to program, or even if you are an experienced programmer who likes the idea of writing programs more easily, Phrogram offers you several important advantages: Phrogram makes it easy and fun to learn programming. Phrogram is "plain language"--that is, it uses descriptive, intuitive names, and it keeps special formatting and strange language keywords to an absolute minimum. Unlike other easy-to-learn languages, Phrogram is similar to the tools that are used by professional programmers today. Phrogram is the easiest way to do real software development--whether or not you are a beginning programmer. This is especially true if you want to create a game or graphical program, although you can design just about any kind of program with Phrogram. And you will find it quicker, more efficient, and easier to do this in Phrogram than in any other language, because that is what Phrogram was specifically and carefully designed to do. If you decide to move on to professional programming, Phrogram prepares you well for widely used professional languages like Java, C#, or Visual Basic. Phrogram provides a complete programming environment that is similar to these languages, but it is much easier to master, and a lot more fun to learn and use. What This Short Cut Covers 3 Introduction 4 Section 1: Typing and Running Your First Program in Phrogram 9 Section 2: How Your First Program Works 19 Section 3: Moving Your UFO on the Screen 30 Section 4: Bouncing Your UFO Around the Screen 44 Section 5: Keyboard Control of Your UFO 60 Section 6: Organize Your Program as It Grows 67 Section 7: UFO Escape! Your First Complete Game! 73 Section 8: Bonus Game: Pong! 95 Appendix A: Phrogram Language Examples 99 Appendix B: Glossary of Programming Terms 105 About the Authors 108.